Electroretinogram and Visual Evoked Potentials in Patients with Type II Diabetes Mellitus - رجب محمود; يوسف حبيب; سعدون أسماء (Latakia University Journal -Medical Sciences Series, 2020)
Aim: To study pattern electroretinogram (PERG) and pattern reversal visual evoked potentials (PRVEP) in type 2 diabetic patients without retinopathy (DR) or with mild DR to detect changes by comparing with those of healty controls. And to assess the correlation of parameters with diabetes duration and the level of HbAlc.